Environmental geology - Montgomery, Carla W. 1951- (McGraw-Hill, 2014)
"Preface about the course environmental geology is geology applied to living. The environment is the sum of all the features and conditions surrounding an organism that may influence it. An individual's physical environment encompasses rocks and soil, air and water, such factors as light and temperature, and other organisms. One's social environment might include a network of family and friends, a particular political system, and a set of social customs that affect one's behavior. Geology is the study of the earth. Because the earth provides the basic physical environment in which we live, all of geology might in one sense be regarded as environmental geology. However, the term environmental geology is usually restricted to refer particularly to geology as it relates directly to human activities, and that is the focus of this book. Environ- mental geology is geology applied to living. We will examine how geologic processes and hazards influence human activities (and sometimes the reverse), the geologic aspects of pollution and waste-disposal problems, and several other topics"--Provided by publisher.